Failure and root cause analysis of vehicle drive shaft. (May 2019) - Zhao, Li-Hui; Xing, Qing-Kun; Wang, Jia-Yu; Li, Shen-Long; Zheng, Song-Lin
Abstract: This paper investigates the failure mode and root cause of drive shaft failure in a vehicle through examination of the macroscopic and microscopic morphologies of the fracture surface, the chemical composition, metallographic analysis, and mechanical properties of the material, and theoretical finite element calculations of the drive shaft. The results show that fatigue was the dominant mechanism of drive shaft failure due to obvious benchmarks on the fracture surfaces. Fatigue cracks initiated from the root fillet region of the spline gear. The absence of material defects in this region indicates that the main cause of fatigue cracks is attributable to a high stress concentration owing to the small geometrical dimensions of the root fillet. Meanwhile, the poor quality of the root fillet due to relatively high manufacturing tolerances also produces a higher stress concentration, and thus accelerates crack initiation and propagation. Furthermore, all the fatigue fractures occur on the right splines owing to higher stress amplitudes at this location. Improper stiffness matching between the left and right smooth shafts, which results in a larger torque transmitted to the right spline, is the root cause of the drive shaft failure. These results indicate that re-evaluating drive shaft design to ensure an equal stiffness between the two smooth shaft sections is recommended for a longer service life. Highlights: The dominant mechanism of failure involved high cycle fatigue resulting from cyclic stress amplitudes less than the YS of the material. The fatigue crack nucleated at the root fillet of the right spline where the stress concentration was higher. The high stress on right splines results from the higher torque than the left due to asymmetrical stiffness on the shaft. This unexpected type of early fatigue failure could be avoided by a new design which considers the torque distribution.